Codeveloping an effective EMPA to maturity in an acute NHS Trust: an implementer report. Issue 1 (4th January 2022) - Silva, Geeth; Bourne, Tim; Hall, Graeme; Patel, Shriyam; Rauf, Mohammed Qasim; Vogel, Aaron; Carruthers, Andrew; Xu, Gang
Abstract : Introduction: University Hospitals Leicester has codeveloped, with Nervecentre, an Electronic Prescribing and Medicines Administration System that meets specific clinical and interoperability demands of the National Health Service (NHS). Methods: The system was developed through a frontline-led and agile approach with a project team consisting of clinicians, Information Technology (IT) specialists and the vendor's representatives over an 18-month period. Results: The system was deployed successfully with more than a thousand transcriptions during roll-out. Despite the high caseload and novelty of the system, there was no increase in error rates within the first 3 months of roll-out. Healthcare professionals perceived the new system as efficient with improved clinical workflow, and safe through an integrated medication alert system. Discussion: This case study demonstrates how NHS trusts can successfully co-develop, with vendors, new IT systems which meet interoperability standards such as Fast Healthcare Interoperability Resources, while improving front line clinical experience. Conclusion: Alternative methods to the 'big bang' deployment of IT projects, such as 'gradual implementation', must be demonstrated and evaluated for their ability to deliver digital transformation projects in the NHS successfully.